MARKET SEGMENTATION OF SOCIAL MEDIA IN INDONESIA - Heryono, Heri (CENTRAL ASIA AND THE CAUCASUS, 2022)
The use of social media emerges various terms of its segmentation, market and demographic characteristics attached to personal attribute. Social media lead to a space where users could share things, moment and perspective. It realizes the potential for a lot of information that can be extracted from social media. This research purposes to disclose the market segmentation of several social media commonly accessed in Indonesia; it involves Instagram, Facebook and Reddit. Theories applied for this research are [1]dealing with market segmentation of social media users and [2] regarding to words choice and personality of social media users. This research purposes to observe personal characteristics of social media users and to map the coverage of social media to their users, especially in Indonesia. It involves 102 participants came from various level of age and different background of interest. Results of the research shows that the most social media regularly opened and accessed by younger-aged participants is Reddit for 77%; while Instagram is commonly accessed by participants aged 27-35 for about 22%; and Facebook has loyal users commonly aged 40 and above for 11%. It can be concluded that Reddit relates to younger users as its market segment; in other words, the contents represent contemporary and modern topics interesting for younger users.